Graphene oxide layers modified by irradiation with 1.0 MeV Au+ ions. (28th May 2018) - Malinský, Petr; Cutroneo, Mariapompea; Macková, Anna; Hnatowicz, Vladimir; Szökölová, Kateřina; Bohačová, Marie; Luxa, Jan; Sofer, Zdeněk
Abstract : Graphene oxide (GO) foils were modified by irradiation using 1.0 MeV Au + ions, and their elemental composition before and after the ion irradiation was investigated using Rutherford back‐scattering spectroscopy (RBS). The surface morphology was studied using SEM, and changes in elemental composition and structure of GO in shallow subsurface were characterized by various spectroscopy techniques including X‐ray photoelectron spectroscopy and Raman spectroscopy. Electrical properties were determined using standard 2‐point method. The analyses indicate that the Au irradiation up to 1.0 × 10 15 cm −1 results in removal of oxygen functionalities and growth of graphene domains, leading to a surface conductivity increase dependent on the applied ion fluence. The Au irradiation with excessive ion fluencies leads to the amorphization of GO foil structure.